PEMANFAATAN ZINGEBERACEAE OLEH MASYARAKAT KAMPUNG MISABNGOISI DAN KAMPUNG BINGWOYUT DISTRIK MINYAMBOUW KABUPATEN MANOKWARI - Obeth Ullo; Simon Sutarno; Fajar RDN Sianipar (VOGELKOP: Jurnal Biologi, 2023)
Hattam tribe is one of the tribes who inhabited the area in the mountains of West Papua in Manokwari District Arfak. Hattam tribes have different knowledge of plants used in everyday life because of its dependence on the natural wealth of the high forest. This study aims to determine which species Zingiberaceae used by the community in Kampung Misabngoisi Tribe Hattam and Bingwoyut Minyambouw Manokwari District and to the value of each plant species exploited. The study took place from the date of February 10 to March 10 2010 with using descriptive method with field observation techniques and semi-structural interviews based on questionnaires that had been prepared. The results obtained show that societies Hattam Tribe who live in Kampung Bingwoyut Misabngoisi and utilize nine Zingiberaceae species as drugs - drugs, three species as spices, food ingredients and mystical, while each - each one species. When viewed from the value of benefits, the species has The highest value of benefits by the Village and Bingwoyut Misabngoisi is Zingiber officinale. While for the species having the lowest value of benefits in Kampung Misabngoisi is Hedychum coronarium and Kampung Bingwoyut is Pluranthodium sp.2.